2022
DOI: 10.1111/jam.15468
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of environmental conditions as a decontamination approach for SARS-CoV-2 when applied to common library, archive and museum-related materials

Abstract: Aims:The purpose of this study was to evaluate the effects of ambient or altered environmental conditions on the inactivation of SARS-CoV-2 applied to materials common in libraries, archives and museums. Methods and Results:Porous and non-porous materials (e.g. paper, plastic protective book cover) were inoculated with approximately 1 × 10 5 TCID 50 SARS CoV-2 (USA-WA1/2020), dried, placed within test chamber in either a stacked or unstacked configuration, and exposed to environmental conditions ranging from 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 51 publications
(51 reference statements)
0
4
0
Order By: Relevance
“…Various studies have been investigated the lifetime of SARS-CoV-2 on porous and non-porous surfaces. 132 The results have shown that viable viruses cannot be found on porous surfaces for minutes to hours; however, viruses may be detected on non-porous surfaces for days to weeks, according to the findings. [133][134] Because of capillary action inside pores and quicker aerosol droplet evaporation, it is possible that SARS-CoV-2 inactivation occurs more quickly on porous surfaces than on non-porous surfaces when compared with non-porous surfaces.…”
Section: Virus Elimination By Metallic Oxides Nanoparticlesmentioning
confidence: 82%
“…Various studies have been investigated the lifetime of SARS-CoV-2 on porous and non-porous surfaces. 132 The results have shown that viable viruses cannot be found on porous surfaces for minutes to hours; however, viruses may be detected on non-porous surfaces for days to weeks, according to the findings. [133][134] Because of capillary action inside pores and quicker aerosol droplet evaporation, it is possible that SARS-CoV-2 inactivation occurs more quickly on porous surfaces than on non-porous surfaces when compared with non-porous surfaces.…”
Section: Virus Elimination By Metallic Oxides Nanoparticlesmentioning
confidence: 82%
“…Having LAVs for COVID-19 is critical because LAVs could be safe, effective, and affordable for LMICs. It can be stored and transported at −20 °C but does not require −70 °C (for mRNA vaccines) due to the stability of SARS-CoV-2 [ 59 , 60 ]. Such a cold chain is currently used for the polio LAVs in the polio eradication campaign in many developing countries [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent works report that the virus decreases its infectivity when exposed to solar radiation [20] and UV-C radiation [21,22] at ground level. Even when the virus is exposed to UV-A (the terrestrial UV radiation) over 15 min, the virus inactivation happens [23], even in aerosols [24].…”
Section: Sars-cov-2 Meteorological Parameters Effectmentioning
confidence: 99%